System Digital Payments : A Critical Review Literature about Trends and Challenges Moment This - Aminah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The digital payment system has revolutionized financial transactions, offering various methods such as mobile payments, contactless transactions, and blockchain-based solutions. This literature review critically examines the current trends and challenges in digital payment systems. The study employs a comprehensive review methodology to analyze key trends, including the rapid growth of mobile payments, the adoption of contactless payments, the role of cryptography and blockchain, and the evolution of cross-border payments and digital remittances. Key challenges identified include data security and privacy, regulatory compliance, financial inclusion, and interoperability. The results highlight the need for technological innovation, stakeholder collaboration, enhanced financial literacy, and supportive regulatory frameworks to address these challenges and maximize the potential of digital payment systems.